Do guided internet-based interventions result in clinically relevant changes for patients with depression? An individual participant data meta-analysis. (July 2018) - Karyotaki, Eirini; Ebert, David Daniel; Donkin, Liesje; Riper, Heleen; Twisk, Jos; Burger, Simone; Rozental, Alexander; Lange, Alfred; Williams, Alishia D.; Zarski, Anna Carlotta; Geraedts, Anna; van Straten, Annemieke; et al.
Abstract: Little is known about clinically relevant changes in guided Internet-based interventions for depression. Moreover, methodological and power limitations preclude the identification of patients' groups that may benefit more from these interventions. This study aimed to investigate response rates, remission rates, and their moderators in randomized controlled trials (RCTs) comparing the effect of guided Internet-based interventions for adult depression to control groups using an individual patient data meta-analysis approach. Literature searches in PubMed, Embase, PsycINFO and Cochrane Library resulted in 13, 384 abstracts from database inception to January 1, 2016. Twenty-four RCTs (4889 participants) comparing a guided Internet-based intervention with a control group contributed data to the analysis. Missing data were multiply imputed. To examine treatment outcome on response and remission, mixed-effects models with participants nested within studies were used. Response and remission rates were calculated using the Reliable Change Index. The intervention group obtained significantly higher response rates (OR = 2.49, 95% CI 2.17–2.85) and remission rates compared to controls (OR = 2.41, 95% CI 2.07–2.79). The moderator analysis indicated that older participants (OR = 1.01) and native-born participants (1.66) were more likely to respond to treatment compared to younger participants and ethnic minorities respectively. Age (OR = 1.01) and ethnicity (1.73) also moderated the effects of treatment on remission.Moreover, adults with more severe depressive symptoms at baseline were more likely to remit after receiving internet-based treatment (OR = 1.19). Guided Internet-based interventions lead to substantial positive treatment effects on treatment response and remission at post-treatment. Thus, such interventions may complement existing services for depression and potentially reduce the gap between the need and provision of evidence-based treatments. Highlights: Little is known about clinically relevant changes in guided Internet-based interventions. Guided Internet-based interventions result in significantly higher remission and response compared to controls Severity of depression, age and ethnicity significantly moderate treatment outcome.